Deviant Peer Associations and Perceived Police Legitimacy: Is There a Connection?. (October 2019) - Ferdik, Frank Valentino; Gist, Jon; Evans, Sara Z.
For police officers to effectively enforce the law, it is imperative that citizens perceive of them as legitimate authority figures. Although procedural justice has shown to be a salient predictor of perceived police legitimacy, a recent line of studies has discovered other significant correlates of this outcome. No study though has explored whether deviant peer associations share a relationship with law enforcement legitimacy evaluations. Questionnaire data were collected from a convenience sample of university students ( N = 623) to determine whether measures of friend's attitudes favorable toward criminal acts as well as friend's actual criminal behaviors predicted both the obligation to obey and trust in police constructs of police legitimacy. Results indicated that friend's attitudes supportive of criminal behaviors negatively predicted each police legitimacy concept, while somewhat unexpectedly, respondents who reported having many friends who engaged in past crimes were more likely to obey the police. Policy implications are discussed.